The Effectiveness of KWL Strategy for Reading Comprehension - Faudi Faudi; Lia Erlisa; Isnaini Putri; Mouna Lidza; Cici Orensi (Universitas Serambi Mekkah, 2020)
Some strategies used by teachers when teaching English seemed to be less effective, causing the students to have a comprehension difficulty, including in reading. This issue was also found among the students of SMA Negeri 1 Darul Imarah, Aceh Besar. This study was therefore conducted to find out whether or not the eleventh grade students of SMA Negeri 1 Darul Imarah taught reading comprehension by using KWL Strategy will receive a higher score than those taught without KWL Strategy. This study used the quantitative method with experimental design. Sixty students were taken as the sample. The data were analyzed by using t-test, and the result showed that the t-score of two means between post-test of experimental and control group was 2.19 thus, the t-test was higher than the critical value of the t-test for the degree freedom of 58 (167) at the level of significance 0.05.